Study Of School Environmental Sanitation In SMP Negeri 34 Padang - Oktaviana, Marisa; Handayani, Fitri; Syampurma, Hilmainur (Jurnal Guru Peneliti Professional, 2018)
This research is motivated by the lack of environmental sanitation facilities and inadequate school health efforts on student health. This is thought to be caused by many factors, one of which is a study on the management of school environmental sanitation. The objectives of this study were 1) Knowing how the implementation of environmental sanitation at SMP Negeri 34 Padang, 2) Knowing the existence of environmental sanitation facilities and infrastructure at SMP Negeri 34 Padang, and 3) Knowing the quality of environmental facilities and infrastructure at SMP Negeri 34 Padang. This research is descriptive in nature, namely research that aims to explain the management of environmental sanitation and school health efforts. The population in this study were all class VII students totaling 60 people consisting of 27 sons and 33 daughters. Sampling was carried out using the Morandown Sampling technique in which part of the population was sampled. Data obtained by using primary data and secondary data. From the research results obtained the results of the questionnaire where from 20 students with 15 questionnaire questions obtained results 65.67% who answered there was still something related to environmental sanitation. And 34.33% of the 20 students answered none. In connection with these findings, several efforts were suggested to school principals, teachers, administrators, students and those concerned with school environmental sanitation to pay attention to student health.